Habitat choice in ciliate microcosms experiment - Jacob, Staffan; Legrand, Delphine; Chaine, Alexis S; Bonte, Dries; Schtickzelle, Nicolas; Huet, Michèle; Clobert, Jean (In supplement to: Jacob, S et al. (2017): Gene flow favours local adaptation under habitat choice in ciliate microcosms. Nature Ecology & Evolution, 1(9), 1407-1410, https://doi.org/10.1038/s41559-017-0269-5, 2017)
Cells that chose to stay in or join the thermal niche margin through dispersal have higher fitness in these marginal conditions than those that chose the other habitat. Treat = patch chosen by cells in the 3-patch systems (e.g. r23_d35 = dispersal from a 23°C patch toward a 35°C patch; r23 = residents in a 23°C patch). Growth rate = fitness estimation of cells from each patch through a quantification of increased optical density per hour from a small number of cells from each patch, fitted from population growth curves using gcfit function (grofit R-package) with spline fit. Patch_chosen = "destination" patch chosen (either by staying in or joining it).